Bistatic P-band SAR for Spacecraft AIST-2. (2015) - Borisenkov, Aleksey; Goriachkin, Oleg; Dmitrenok, Victor; Dolgopolov, Vadim; Zhengurov, Boris; Juravlev, Aleksander; Kurkov, Igor; Khohlov, Sergey
Abstract: This paper describes a Bistatic P - band Synthetic Aperture Radar for spacecraft AIST-2. This system is a special case of multi-system radar remote sensing .The main parameters and purpose the mission AIST -2 are presented.